Video-assisted thoracoscopic right anterior, lateral, and medial segmentectomy for primary lung cancer of the middle lobe with incomplete interlobar fissures - Mizuno, Kotaro; Ohata, Norihisa; Hatou, Motoki; Tanaka, Hironori (Journal of Thoracic Disease, 2017)
A 63-year-old woman was referred to our hospital due to an abnormal shadow in the right middle lung field on chest X-ray. Chest computed tomography revealed a 2.0 cm nodule in the right lateral segment of the middle lobe. The nodule was confirmed to be lung adenocarcinoma by transbronchial lung biopsy. Because the tumor was located near the incomplete interlobar fissures, resection might traditionally be performed by right upper and middle lobectomy. However, we chose a minimally invasive intervention and performed anterior, lateral, and medial segmentectomy under video-assisted thoracic surgery. This technique resulted in complete tumor resection with minimal adverse effects.